The Phenomenon of Artificial Intelligence Hallucination: The Challenge of The Use of Fake Data Towards Lawyer’s Practices According to Indonesia Law - Mutmainnah, Ummu Kaidah (Badan Pembinaan Hukum Nasional, 2024)
This article aims to review how Artificial Intelligence has had a significant impact following the rise of AI Hallucination cases that occurred in lawyering practice. The discussions that will be studied in this research are: 1) what is the legal basis for AI according to law in Indonesia and 2) how the phenomenon caused by artificial intelligence in the form of AI Hallucination can affect the profession of Lawyer as law enforcers. The form of research method used is juridical-normative, through literature studies. The author uses legal materials such as statutory regulations, books and scientific articles that discuss AI and cases of AI Hallucination. From the legal issues mentioned above, research results found in the form of 1) that currently in Indonesia there are no regulations that discuss AI in detail, only that AI can be linked to the ITE Law, PDP Law and Kominfo Circular Letters. 2) The existence of the AI Hallucination phenomenon is a challenge for advocates because fake data resulting from AI hallucination used by an advocate can have a negative impact not only on individuals but also on law enforcement and public trust in the advocate himself